Features of providing information for consumers regarding food products in the conditions of the HACCP - Stukalska (Ivanova), Nataliia; Kuzmin, Oleg; Karpachov, Oleksandr (My University, 2022)
Starting from 2016, Ukraine gradually began to apply and implement the HACCP system. According to this system, all operators of the food market must implement hygienic requirements in production, the so-called prerequisite programs, and implement procedures based on the principles of HACCP.
Keywords: кафедра технології ресторанної і аюрведичної продукції; HACCP system; providing information; consumers; food products